Smash Techniques in Volleyball Games - Sahabuddin, Sahabuddin; Pujianto, Dian; Gani, Ruslan Abdul (Sains Global Institut, Indonesia, 2023)
This research aims to determine the relationship between arm explosive power, leg explosive power, and hand-eye coordination with smash ability in volleyball. The population in this study were all FIK UNM sports coaching education students with a total research sample of 30 students selected by random sampling. The data analysis technique used is correlation and regression analysis techniques using the SPSS Version 21.00 system at a significance level of 95% or α 0.05. Based on the results of data analysis, this study concluded that: (1) there is a significant relationship between arm explosive power and smash ability in volleyball, proven to be r0 = 0.955 (P < α 0.05), (2) there is a significant relationship between power leg explosiveness and smash ability in volleyball, proven to be r0 = 0.957 (P < α0.05), (3) there is a significant relationship between hand-eye coordination and smash ability in volleyball, proven to be r0 = 0.852 (P < α0.05 ), (4) there is a significant relationship between arm explosive power, leg explosive power and hand-eye coordination with smash ability in volleyball, proven to be R0 = 0.970 (P < α 0.05).